2019
DOI: 10.1002/cncr.31978
|View full text |Cite
|
Sign up to set email alerts
|

Targeting autophagy using natural compounds for cancer prevention and therapy

Abstract: Autophagy, also known as macroautophagy, is a tightly regulated process involved in the stress responses, such as starvation. It is a vacuolar, lysosomal pathway for the degradation of damaged proteins and organelles in eukaryotic cells. Autophagy also plays a key role in various tissue processes and immune responses and in the regulation of inflammation. Over the past decade, three levels of autophagy regulation have been identified in mammalian cells: 1) signaling, 2) autophagosome formation, and 3) autophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
198
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(201 citation statements)
references
References 231 publications
3
198
0
Order By: Relevance
“…34,35 Several reports have highlighted the participation of autophagy regulation in different cancers, including OS. 36,37 In the present study, we showed that miR-193b significantly increases the expression of autophagy-related proteins in OS cells and promotes cell sensitivity to epirubicin treatment, indicating that miR-193b-induced OS cell apoptosis may be autophagy-dependent.…”
Section: Discussionsupporting
confidence: 49%
“…34,35 Several reports have highlighted the participation of autophagy regulation in different cancers, including OS. 36,37 In the present study, we showed that miR-193b significantly increases the expression of autophagy-related proteins in OS cells and promotes cell sensitivity to epirubicin treatment, indicating that miR-193b-induced OS cell apoptosis may be autophagy-dependent.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, emerging studies have demonstrated a link between autophagy and apoptosis. [39][40][41][42] Atg7, an essential autophagy regulator, plays important roles in disease development and progression. 31,33 In this study, we used ATG7 siRNA and 3-MA to inhibit autophagy and explore the potential role of autophagy in NaB-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…38 However, autophagy plays a dual role in cancer development and progression and is a vital target in human disease prevention and therapy. 39 Autophagy can not only promote apoptosis or induce autophagic cell death to suppress the development of malignancy but also degrade and recycle cellular components to maintain homeostasis and promote tumor cell survival. 40 A study reported that inhibition of autophagy diminishes apoptosis in human osteosarcoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is a evolutionarily conserved process for cells in defense of environmental stress, which degraded and reused the destructed cellular constitutes and cytoplasmic organelles to protect cells from death [13,14]. Recent data agreed that LC3 (microtubule-associated protein light chain 3) and p62 could be used to test autophagy activities, and increase of LC3-II (membrane bound)/LC3-I (cytosolic section), and degradation of p62 indicated activation of autophagy ux [15,16].…”
Section: Ed Thatmentioning
confidence: 99%